PENGARUH MUSIK SEBAGAI MEDIA RELAKSASI MAHASISWA BARU - Arcita, Gabriela Nofel; Adisurya, Ahmad Najla Fikriya; Setiaji, Bayu (Jurnal Penelitian Musik, 2025)
Academic pressure, social demands, and the adjustment process during the transition from high school to college can cause stress, anxiety, and mental fatigue for new students. This research aims to determine the effect of music as a relaxation medium for students. The research used a questionnaire that was asked of 30 respondents. The results show that music can reduce stress levels because it improves students' mood and calms them. Students choose Pop, Instrumental and Jazz music genres to reduce stress because the melody, rhythm and tempo match with the mood students feel when they are stressed. Apart from that, in pop music, the lyrics have meaning and are related to the mood that is being experienced by the students.